Faktor yang Berhubungan dengan Kasus Skizofrenia - Dilfera Hermiati; Resnia Madona Harahap (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to study the factors associated with the incidence of schizophrenia in patients in the Soeprapto Mental Hospital of Bengkulu Province. The method used is descriptive research design using cross sectional. The analysis showed that most of the respondents were 39 people (58.2%) who used schizophrenia, most of the respondents were 15 people who were genetic factors, most of the respondents were 24 people who were psychosocial factors, and some of the respondents were 24 people who have environmental factors. Conclusion, there is a significant relationship between genetics and schizophrenia, there is a significant relationship between psychosocial and schizophrenia, and there is a significant relationship between the environment and schizophrenia in patients in the inpatient ward of Soeprapto Bengkulu Province. Keywords: Genetic, Environment, Psychosocial, Schizophrenia